Risk Factors for Recurrences of Pulmonary TB among Patients in Denpasar: A Case-Control Study - Ni Luh Putu Karminiasih; I Wayan Gede Artawan Eka Putra; Dyah Pradnyaparamita Duarsa; Ida Bagus Ngurah Rai; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: The incidence of recurrence in patients with pulmonary tuberculosis (TB) in Denpasar in 2014 was relatively high, around 3.5% of 1082 patients. This study aims to determine the risk factors for recurrence of pulmonary TB patients in Denpasar. Methods: The study design was a case control with 46 patients with pulmonary TB recurrence aged over 15 years as cases, and 92 patients who had recovered as control. Respondents were selected using systematic random sampling from the TB register from 2013 to 2015 in public health centers in Denpasar. Data were collected by a search of documents, observations, measurements and interviews conducted using questionnaires. Bivariate and multivariate analysis were conducted using chi square test and logistic regression respectively. Results: Risk factors that associated with recurrence of pulmonary TB were co-morbidity of diabetes mellitus (AOR=9.6; 95%CI: 2.17-43.08), adherence (AOR=7.6; 95%CI: 2.85-20.17), exposure to cigarette smoke during treatment (AOR=3.6; 95%CI: 1.41-9.16), home ventilation <10% (AOR=3.4; 95%CI: 1.27-9.47), house contact with pulmonary TB patients (AOR=3.1; 95%CI: 1.31-7.46) and malnutrition (AOR=2.8; 95%CI: 1.02-7.72). Conclusion: Risk factors for recurrence of pulmonary TB among patients were co-morbidity of diabetes mellitus adherence, cigarette smoke exposure during the treatment period, home ventilation <10%, house contact with pulmonary TB patients and malnutrition.